An improved behavioural assay demonstrates that ultrasound vocalizations constitute a reliable indicator of chronic cancer pain and neuropathic pain - Selvaraj Deepitha; Hildebrandt Ullrich; Nattenmüller Ulrike; Kurejova Martina; Stösser Sebastian; Kuner Rohini (Molecular Pain, 2010)
Abstract Background On-going pain is one of the most debilitating symptoms associated with a variety of chronic pain disorders. An understanding of mechanisms underlying on-going pain, i.e. stimulus-independent pain has been hampered so far by a lack of behavioural parameters which enable studying it in experimental animals. Ultrasound vocalizations (USVs) have been proposed to correlate with pain evoked by an acute activation of nociceptors. However, literature on the utility of USVs as an indicator of chronic pain is very controversial. A majority of these inconsistencies arise from parameters confounding behavioural experiments, which include novelty, fear and stress due to restrain, amongst others. Results We have developed an improved assay which overcomes these confounding factors and enables studying USVs in freely moving mice repetitively over several weeks. Using this improved assay, we report here that USVs increase significantly in mice with bone metastases-induced cancer pain or neuropathic pain for several weeks, in comparison to sham-treated mice. Importantly, analgesic drugs which are known to alleviate tumour pain or neuropathic pain in human patients significantly reduce USVs as well as mechanical allodynia in corresponding mouse models. Conclusions We show that studying USVs and mechanical allodynia in the same cohort of mice enables comparing the temporal progression of on-going pain (i.e. stimulus-independent pain) and stimulus-evoked pain in these clinically highly-relevant forms of chronic pain.